PENGARUH TATA KELOLA PEMERINTAHAN DESA: STUDI KORELASIONAL ANTARA TRANSPARANSI, AKUNTABILITAS, DAN PENGELOLAAN APBDES DI GAMPONG COT LAOT - Zalikha , Zalikha; Ariska, Emalia; Yusuf, M.; Mulyadi , Mulyadi; Muchsin , Muchsin (Bussman Journal : Indonesian Journal of Business and Management, 2025)
The management of APBDes funds signifies that all planning, which is the result of an agreement between the village government and the village consultative body, encompasses expenditures stipulated for the administration of village governance for one year. The objective of this research is to analyze the influence of village government transparency and accountability on the management of the village revenue and expenditure budget (APBDes) in Gampong Cot Laot, Peudada Subdistrict, Bireuen Regency. To obtain optimal results, the data scope was derived from respondent answers through questionnaire questions distributed to 40 respondents, namely the community of Cot Laot Village, Peudada Subdistrict, Bireuen Regency. The data analysis technique used in this research is multiple linear regression. The research results, both partially and simultaneously, indicate that village government transparency and accountability have a positive and significant influence on the management of APBDes in Cot Laot Village, Peudada Subdistrict, Bireuen Regency.